Applications of the spline filter for areal filtration. (4th November 2015) - Tong, Mingsi; Zhang, Hao; Ott, Daniel; Chu, Wei; Song, John
Abstract: This paper proposes a general use isotropic areal spline filter. This new areal spline filter can achieve isotropy by approximating the transmission characteristic of the Gaussian filter. It can also eliminate the effect of void areas using a weighting factor, and resolve end-effect issues by applying new boundary conditions, which replace the first order finite difference in the traditional spline formulation. These improvements make the spline filter widely applicable to 3D surfaces and extend the applications of the spline filter in areal filtration.